Can strengthening digital infrastructure enhance productivity in the cultural industry? evidence from Tibet - Yuanyuan Li; Qianqian Du; Guihua Ma; Caidan Gazang (PLoS ONE, 2025)
This study, grounded in the Total Factor Productivity (TFP) theoretical framework, examines the impact of digital infrastructure on the productivity of Tibet’s cultural industry from 2011 to 2021. It aims to uncover how the innovative allocation of production factors can enhance new-quality productivity. The core aspect of new-quality productivity is the improvement of TFP, with digital infrastructure promoting the cultural industry’s development by optimizing industrial agglomeration, improving logistics efficiency, and reducing the urban-rural consumption gap. The findings suggest that while digital infrastructure leads to geographic dispersion of the industry—challenging traditional industrial agglomeration theory—it significantly enhances the efficiency of the cultural industry within Tibet’s unique socio-economic context. Moreover, despite the region’s geographical constraints on logistics efficiency, digital platforms effectively reduce the urban-rural consumption gap, improving market access and the quality of cultural services in remote areas. Additionally, digital infrastructure helps bridge the digital divide between urban and rural areas, further fostering balanced regional consumption and digital inclusion. From a Total Factor Productivity perspective, this study reveals key pathways to improving new-quality productivity, offering both theoretical foundations for policymakers and practical guidance for the development of cultural industries in similarly structured regions.